2012
DOI: 10.1002/jrs.4226
|View full text |Cite
|
Sign up to set email alerts
|

Colour diversification in octocorals based on conjugated polyenes: A Raman spectroscopic view

Abstract: Polyenic pigments in octocorals have been investigated by Raman spectroscopy using laser excitation at 532, 785 and 1064 nm. The spectral features suggest the structural nature of carotenoids from Phyllogorgia dilatata, Leptogorgia punicea, Muricea atlantica, Carijoa riisei and conjugated polyenals from L. punicea, L. setacea, Muricea flamma and Renilla muelleri. The observed vibrational bands at ca. 1540–1520 ν1(C=C), 1159 ν2(C–C) and 1005 cm−1 ρ3(C–CH3) were assigned to carotenoids, whereas the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 63 publications
1
48
0
Order By: Relevance
“…[21,25]. Previous works from Maia et al [27,29] and comparison with the literature data [13] have demonstrated that the red octocoral L. punicea may contain 11 conjugated double bonds due to the presence of ν(C=C) modes at ca 1509 cm −1 . However, deconvolution of the in situ Raman spectra using the 1064 nm laser line for vibrational modes ranging from 1550 to 1480 cm −1 and from 1040 to 980 cm −1 showed two distinct bands.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[21,25]. Previous works from Maia et al [27,29] and comparison with the literature data [13] have demonstrated that the red octocoral L. punicea may contain 11 conjugated double bonds due to the presence of ν(C=C) modes at ca 1509 cm −1 . However, deconvolution of the in situ Raman spectra using the 1064 nm laser line for vibrational modes ranging from 1550 to 1480 cm −1 and from 1040 to 980 cm −1 showed two distinct bands.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectra of polyenals identified from certain octocorals, such as Leptogorgia setacea, M. flamma, R. muelleri, L. punicea (figure 2), Chromonephthea braziliensis and Phyllogorgia dilatata (not shown) [27][28][29], presented spectral features resembling those of Corallium spp. [21,25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies involving marine organisms are emerging, and Raman analysis has been applied to animals, algae, and dinoflagellates, which have identified carotenoids, sterols, nonsubstituted conjugated polyenals, chromophores of green fluorescent proteins (GFPs), chlorophylls, melanins, and mycosporine-like amino acids (MAAs). Carotenoids have been identified from corals [140][141][142], mollusks [143,144], lobster carapace [145,146], fish [147], brown algae [148] and dinoflagellates [149]. Polyenals are a recently described class of polyenes identified from shells of mollusks [143,144] and octocorals [140][141][142][150][151][152][153].…”
Section: Application Of Raman Scattering To Marine Natural Products: mentioning
confidence: 99%